1976
DOI: 10.1002/jsfa.2740270217
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of some volatile nitrosamines in cooked bacon

Abstract: Bacon was fried in the normal UK domestic manner, and the rashers, the cooked-out fat and the vapour were analysed for N-nitrosopyrrolidine and N-nitrosodimethylamine. Quantitative results were based on high resolution mass spectral measurements, and it was found that for both of the nitrosamines by far the greatest proportion occurred in the vapour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Sen et al (1976a) found, on average, about 70% of the total NDMA and 50% of the total NPYR in the vapor produced during cooking, in reasonable agreement with our results. In contrast, Gough et al (1976) reported that the majority of their samples showed >85% of the NDMA and >75% of the NPYR in the vapors. It is possible that the disagreement with the data presented by the English workers is due to the different types of bacon used.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Sen et al (1976a) found, on average, about 70% of the total NDMA and 50% of the total NPYR in the vapor produced during cooking, in reasonable agreement with our results. In contrast, Gough et al (1976) reported that the majority of their samples showed >85% of the NDMA and >75% of the NPYR in the vapors. It is possible that the disagreement with the data presented by the English workers is due to the different types of bacon used.…”
Section: Resultsmentioning
confidence: 91%
“…Two methods were used to collect the volatiles from frying bacon. In the first method we collected the volatiles to determine the distribution of nitrosamines between the vapor and the cook-out fat in a manner similar to that reported by Gough et al (1976). The exact details of the method used and the results of our work are available in the supplemental section (see Supplementary Material Available paragraph).…”
mentioning
confidence: 99%
“…Trace levels of volatile iV-nitrosamines have been reported in cured meat products (Gough et al 1976) which have also been shown to contain A^-nitrosoamino acids (Janzowski et al 1978). In the last two years iV-nitrosothiazolidine (NTHZ) has been identified in fried bacon (Gray et al 1982, Kimoto et al 1982.…”
Section: Introductionmentioning
confidence: 98%
“…Most processed poultry products are formulated with some level of added nitrite. Concern has been expressed regarding the use of nitrite in processed meat products since the nitrite can be converted to nitrosamines during cooking (Gough et al, 1976;Gray and Randall, 1979;Pensabene et al, 1974;Nakamura et al, 1976;Wasserman e t al., 1978).…”
Section: Introductionmentioning
confidence: 99%